Circles on pommel horse with a suspended aid: Mass-centre rotation and hip joint moment - Fujihara, T.; Gervais, P. (Journal of Sports Sciences, 2012)
This is the second study of the series, and its aim was to investigate the influence of using the suspended aid on circle kinetics. In addition to the kinematic data recorded for part one (Fujihara & Gervais, 2012), the pommel reaction forces and the force applied from the suspended aid (aid reaction force) were analysed in relation to the motion of a whole-body mass centre. The hip joint moment was also computed by combining all segments in the lower extremities into a single rigid segment. Generally, the use of the aid changed the magnitude of the mass-centre trajectory or horizontal pommel reaction forces but not their patterns. The results also showed that the net hip joint moment was altered during circles with the aid. In summary, a suspended aid can be used as a progression for a variety of goals because it allows gymnasts to practise circles which would not be possible without the aid. When a suspended aid is used, however, practitioners should be aware of the possible kinetic alteration caused by the external force from the aid.